IPTEKS bagi Masyarakat (IbM) Kelompok Ibu-Ibu Rumah Tangga Desa Banjarejo Kecamatan Ngadiluwih Kabupaten Kediri - Mochamad Syaiful Arif (Asian Journal of Innovation and Entrepreneurship, 2017)
These outreach activities conducted in the framework of community empowerment of Banjarejo village, Ngadiluwih district, Kediri Regency. Banjarejo village is one of the villages that are in Ngadiluwih Subdistrict, district of Kediri. Banjarejo village has an area of 3 km2 with a population of 4800 inhabitants and 1353 households. The community of the village Banjarejo the majority of the profession as farmers (especially sugar cane farmers) and the land that is tilled land belonging to other people, so the resulting income is for the results with the landlord. Mothers day activities in the hamlet of Banjarejo is as housewives, so that family income depends only on the results of farming done the head of the family. Low productivity and earnings are still below the average UMK (Minimum Wage) make the economic conditions of the community of the village Banjarejo are below average. The low income community also makes it difficult to create field efforts independently. The situation of the Islamic religion which is very pronounced in the environs of the village made the village Banjarejo has the potential of local wisdom. In addition, sewing skills possessed some housewives in the hamlet of Banjarejo can provide potential business ventures. These outreach activities aim to increase productivity and income through Banjarejo Village society empowerment mother-housewife. By using the minimum skills in terms of tailoring which dikolaborasikan with the local wisdom, then tailoring business activities diwujudkanlah fashions will be done by a group of mothers of households of the village Banjarejo. Partners are divided into two groups, each group consists of three cadres housewife. Activities carried out through counseling, capital assistance, training and mentoring. Outreach is done in order to add insights about the fashion and entrepreneurship. Capital assistance granted to support operational business activities in the form of a sewing machine and raw fabric and yarn. Training conducted to improve the competencies of the partners in terms of tailoring and management efforts. Whereas mentoring is done to maintain consistency, help overcome difficulties and give the spirit of trying to group partners. The result of this activity is to increase the productivity and income of the Group assisted SMEs. Furthermore, the results of these activities are expected to create employment for the whole community of the village Banjarejo, so there is an increase in earnings and productivity for the whole community of the village Banjarejo. Development of business activities can create a hub of muslim fashion in the hamlet of Banjarejo so that it will come true convection tourism for domestic and foreign tourists.